Functional cortical changes in relapsing-remitting multiple sclerosis at amplitude configuration: a resting-state fMRI study - Liu H; Chen H; Wu B; Zhang TJ; Wang J; Huang KX; Song GJ; Zhan J (Neuropsychiatric Disease and Treatment)
Heng Liu,1,* Hua Chen,1,* Bo Wu,1 Tijiang Zhang,1 Jinhui Wang,2,3 Kexin Huang,1 Ganjun Song,1 Jian Zhan4 1Department of Radiology, Affiliated Hospital of Zunyi Medical University, Medical Imaging Center of Guizhou Province, Zunyi, Guizhou, 2Department of Psychology, Hangzhou Normal University, 3Zhejiang Key Laboratory for Research in Assessment of Cognitive Impairments, Hangzhou, 4Department of Neurology, Affiliated Hospital of Zunyi Medical University, Zunyi, Guizhou, People’s Republic of China *These authors contributed equally to this work Objective: The aim of this study was to explore the amplitude of spontaneous brain activity fluctuations in patients with relapsing–remitting multiple sclerosis (RRMS) using the amplitude of low-frequency fluctuation (ALFF) method. Methods: ALFF and SPM8 were utilized to assess alterations in regional spontaneous brain activities in patients with RRMS in comparison with healthy controls (HCs). The beta values of altered brain regions between patients with RRMS and HCs were extracted, and a receiver operating characteristic (ROC) curve was generated to calculate the sensitivities and specificities of these different brain areas for distinguishing patients with RRMS from HCs. Pearson correlation analyses were applied to assess the relationships between the beta values of altered brain regions and disease duration and Expanded Disability Status Scale (EDSS) score. Patients and participants: A total of 18 patients with RRMS (13 females; five males) and 18 sex-, age-, and education-matched HCs (14 females; four males) were recruited for this study. Measurements and results: Compared with HCs, patients with RRMS showed higher ALFF responses in the right fusiform gyrus (Brodmann area [BA] 37) and lower ALFF responses in the bilateral anterior cingulate cortices (BA 24 and 32), bilateral heads of the caudate nuclei, and bilateral brainstem. The ROC analysis revealed that the beta values of these abnormal brain areas showed high degrees of sensitivity and specificity for distinguishing patients with RRMS from HCs. The EDSS score showed a significant negative Pearson correlation with the beta value of the caudate head (r=-0.474, P=0.047). Conclusion: RRMS is associated with disturbances in spontaneous regional brain activity in specific areas, and these specific abnormalities may provide important information about the neural mechanisms underlying behavioral impairment in RRMS. Keywords: multiple sclerosis, amplitude of low-frequency fluctuation, receiver operating characteristic, functional magnetic resonance imaging, blood oxygen level dependent, resting state